The Role of Plausibility in the Experience of Spatial Presence in Virtual Environments - Hofer, Matthias; Hartmann, Tilo; Eden, Allison; Ratan, Rabindra; Hahn, Lindsay (Frontiers in Virtual Reality, 2020)
In the present study, we examine the effect of plausibility violations in a virtual environment (VE) on spatial presence. After reviewing research on the association between plausibility and spatial presence, we present a dual-systems approach to understanding the effect of plausibility (or violations thereof) on spatial presence. We conceptualize the feeling of being present in a VE as a lower-order cognitive process. Perceptions of plausibility violations might represent higher-order cognitive processes that could interfere with spatial presence. We present data from an experimental study in which we manipulated the external consistency (i.e., the plausibility) of the VE, cognitive load (to interfere with higher-order cognitive processes), and immersion to examine its effect on spatial presence. Results show that immersion was the most important factor driving the presence experience. We found no difference between low and high plausibility in spatial presence. Subsequent equivalence tests showed that the group exposed to the implausible VE did not feel less present than the group exposed to the plausible VE. We discuss the findings of our studies in the light of our theoretical considerations and previous research.